Endoplasmic Reticulum Stress Is Involved in Glucocorticoid-Induced Apoptosis in PC12 Cells - Shanyong Yi; Weibo Shi; Min Zuo; Songjun Wang; Rufei Ma; Haitao Bi; Bin Cong; Yingmin Li (Analytical Cellular Pathology)
Objective. The present study selected PC12 cells to construct a neuronal injury model induced by glucocorticoids (GC) in vitro, aiming to explore whether the endoplasmic reticulum stress (ERS) PKR-like endoplasmic reticulum kinase (PERK)-activating transcription factor 4 (ATF4)-C/EBP-homologous protein (CHOP) and inositol requirement 1 (IRE1)-apoptosis signal regulating kinase 1 (ASK1)-C-Jun amino-terminal kinase (JNK) signaling pathways are associated with the neuronal injury process induced by GC and provide morphological evidence. Methods. Cell models with different doses and different durations of GC exposure were established. The viability of PC12 cells was detected by the CCK-8 assay, and the apoptosis rate of PC12 cells was detected by the flow cytometry assay. The expression of microtubule-associated protein 2 (Map2); glucocorticoids receptor (GR); cellular oncogene fos (C-fos); and ERS-related proteins, glucose-regulated protein 78 (GRP78), p-PERK, p-IRE1, ATF4, ASK1, JNK, and CHOP, was observed by immunofluorescence staining. Results. The results of immunofluorescence staining showed that PC12 cells abundantly expressed Map2 and GR. The CCK-8 assay revealed that high-concentration GC exposure significantly inhibited the cell viability of PC12 cells. The flow cytometry assay indicated that high-concentration GC exposure significantly increased the apoptosis rate of PC12 cells. Immunofluorescence staining showed that GC exposure significantly increased the expression of C-fos, GRP78, p-PERK, p-IRE1, ATF4, ASK1, JNK, and CHOP. Treatment with ERS inhibitor 4-phenylbutyric acid (4-PBA) and GR inhibitor RU38486 attenuated related damage and downregulated the expression of the abovementioned proteins. Conclusion. High-concentration GC exposure can significantly inhibit the viability of PC12 cells and induce apoptosis. PERK-ATF4-CHOP and IRE1-ASK1-JNK pathways are involved in the above damage process.